2022
DOI: 10.1186/s12911-022-01899-2
|View full text |Cite|
|
Sign up to set email alerts
|

Decision aids linked to the recommendations in clinical practice guidelines: results of the acceptability of a decision aid for patients with generalized anxiety disorder

Abstract: Background Generalized anxiety disorder (GAD) is one of the most prevalent mental health problems. Patients with GAD have unmet needs related to the information received about their disorder, its treatments and their participation in the decision-making process. The aim of this study is to develop and assess the acceptability of a patient decision aid (PtDA) for patients with GAD. Method The PtDA was developed following the International Patient De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Finally, it is worth noting that respondents in our study reported modest levels of decision-aid acceptability, appropriateness, and feasibility (mean range = 3.3-3.7). Previous research on decision-aids for other clinical conditions (e.g., cancer, mental health) have reported high levels of acceptability and feasibility (39)(40)(41). Likewise, patients in a previous study of the decision-aid (and analyses from this study that are underway) indicate high levels of acceptability from the patient perspective, highlighting some divergence in views.…”
Section: Discussionmentioning
confidence: 49%
“…Finally, it is worth noting that respondents in our study reported modest levels of decision-aid acceptability, appropriateness, and feasibility (mean range = 3.3-3.7). Previous research on decision-aids for other clinical conditions (e.g., cancer, mental health) have reported high levels of acceptability and feasibility (39)(40)(41). Likewise, patients in a previous study of the decision-aid (and analyses from this study that are underway) indicate high levels of acceptability from the patient perspective, highlighting some divergence in views.…”
Section: Discussionmentioning
confidence: 49%
“…The development, challenges and research of PDAs for patients with depression can gain from taking inspiration from research on PDAs for somatic conditions such as osteoarthritis and cancer and for other mental disorders such as schizophrenia ( 18 ). Research in this area has shown that patients' experiences, understanding as well as quality of SDM was improved when digital PDAs contained visual aids such as icons and bar charts ( 82 , 83 ). Another helpful feature in this context might be that information is presented in different formats such as writing, video and audio ( 84 , 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PDAs can have incorporated communication aids ( 84 ) and instruction sheets for their implementation in the clinical workflow ( 88 ). Finally, an efficient strategy might be to align PDAs and their development directly with clinical practice guidelines so that the PDAs reflect guideline content and guidelines contain passages on SDM and PDAs ( 82 , 87 , 89 ). This effort might be strengthened by collaborating with initiatives and stakeholders focusing on clinical practice guidelines, SDM and implementation of best available evidence ( 82 , 87 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], it was reported that the Given- and Family Names of the authors were transposed. The correct author list is given in this Correction article and the original article [ 1 ] has been updated.…”
Section: Correction To: Bmc Medical Informatics and Decision Making (...mentioning
confidence: 99%